Linear Patch of Alopecia in a Child: Trichoscopy Reveals the Actual Diagnosis - Sonthalia, Sidharth (Skin Appendage Disord, 2019)
Linear scleroderma en coup de sabre (LSCS) is a clinical variant of morphea that presents with a linear alopecic patch over the frontal scalp. Linear alopecia areata may present as a close differential in the incipient stages of LSCS in the pediatric population, especially when the binding down and pigmentary changes characteristic of LSCS have not developed. Histopathology may also be noncontributory in such scenarios. We hereby report a case of linear alopecia in a 5-year-old Indian girl and highlight the role of trichoscopic evaluation in clinching the diagnosis. This emphasizes the importance of clinicodermoscopic-pathological correlation over clinicopathological correlation for cutaneous diagnosis.